Reduced description of nonequilibrium processes and correlation functions. Divergences and non-analyticity - Sokolovsky, A.I. (Condensed Matter Physics, 2006)
A complete theory for investigation of time correlation functions is developed on the basis of the Bogolyubov
reduced description method proceeding from his functional hypothesis. The problem of convergence in the
theory of nonequilibrium processes and its relation to the non-analytic dependence of basic values of the
theory on a small parameter of the perturbation theory are discussed. A natural regularization of integral
equations of the theory is proposed. In the framework of a model of slow variables (hydrodynamics of a fluid,
kinetics of a gas) a generalized perturbation theory without divergencies is constructed corresponding to a
partial summation in a usual perturbation theory. Properties of Green functions are discussed on the basis of
resolvent formalism for the Liouville operator. A generalized Ernst and Dorfman theory is elaborated allowing
to study the peculiarities of correlation and Green functions and to solve the convergence problem in the
reduced description method. На основi методу скороченого опису Боголобова, що ґрунтується на функцiональнiй гiпотезi, розвивається повна теорiя для дослiдження часових кореляцiйних функцiй. Обговорюється проблема
розбiжностей в теорiї нерiвноважних процесiв та її зв’язок з неаналiтичною залежнiстю основних
величин теорiї вiд малого параметра теорiї збурень. Пропонується природна регуляризацiя iнтегральних рiвнянь теорiї. В рамках моделi повiльних змiнних (гiдродинамiка рiдини, кiнетика газу)
конструюється узагальнена теорiя збурень, яка вiдповiдає частковому сумуванню у звичайнiй теорiї
збурень. Властивостi функцiй Грiна обговорюються на основi формалiзму резольвенти оператора
Лiувiлля. Розробляється узагальнена теорiя Ернста та Дорфмана, яка дозволяє вивчати особливостi кореляцiйних функцiй i функцiй Грiна та розв’язувати проблему збiжностi у методi скороченого
опису